INVESTIGATION OF PHYSICAL AND CHEMICAL PROPERTIES OF CITRONELLA OIL FOR DETERMINING THE CONCENTRATION OF CITRONELLAL COMPOUND - andry tiawan; tutun nugraha; niken t. listyorini (Liaison Journal of Engineering, 2023)
This journal explores the physical and chemical properties of citronella oils extracted from Cymbopogon species, known for their insect-repellent qualities, essential oils and cosmetic applications. The aim is to determine the relation between concentration of citronellal and its properties for further research. The study analyzes density, refractive index, color, solubility, and utilizes GC-MS analysis. Different citronella oil samples with varying citronellal compositions are examined. The results show variations in properties among samples with different concentrations. Density and refractive index had the potential for determining citronellal concentration. GC-MS analysis identifies and quantifies components, with a focus on citronellal. The refractive index is inversely proportional to the concentration. The relation between the value of refractive index and citronella concentration is (y = -0.0002x + 1.4773) with R2 = 0.9934. Refractive index analysis has the strongest potential to be used as field method of measurement due to its higher resolution nature and ease of it use by untrained persons. Keywords: Citronella, Citronellal, Geraniol, Physicochemical Properties, Density, Refractive Index